2000
DOI: 10.1002/(sici)1096-9853(200002)24:2<101::aid-nag55>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

On the volumetric deformation of reconstituted soils

Abstract: This paper reviews the phenomenon of volumetric hardening, which is a common feature of the mechanical behaviour of many geo-materials. Three di!erent material idealizations have been proposed to describe this hardening, and the paper contains the corresponding mathematical formulation. These idealizations vary in their complexity and hence their ability to capture di!erent aspects of real material behaviour. Any of the three postulates can be implemented into most constitutive models. As a demonstration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…However, to avoid excessive complexity in constitutive equations and especially the application in numerical simulation, N is included in the model formulation. Similar approaches were also used by Liu and Carter and Ni et al for modelling reconstituted soils. Substituting Equation into Equation , one has the following explicit formulation for the plastic modulus, H b : Hb=prefix−ζfptrue¯01+e0λkptrue¯0ngvftrueσ¯1Γ()α …”
Section: Fractional Order Constitutive Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…However, to avoid excessive complexity in constitutive equations and especially the application in numerical simulation, N is included in the model formulation. Similar approaches were also used by Liu and Carter and Ni et al for modelling reconstituted soils. Substituting Equation into Equation , one has the following explicit formulation for the plastic modulus, H b : Hb=prefix−ζfptrue¯01+e0λkptrue¯0ngvftrueσ¯1Γ()α …”
Section: Fractional Order Constitutive Modelmentioning
confidence: 95%
“…theoretical, empirical and semi‐empirical approaches) in modelling the cyclic behaviour of granular soils. The first is the theoretical method, including the traditional elastoplasticity , generalized plasticity and bounding surface plasticity models , where the deformation of each loading cycle is strictly counted. This method reveals the deformation mechanism of soils subjected to cyclic loading.…”
Section: Introductionmentioning
confidence: 99%
“…According to Equation (1), the coefficient of friction = 0.37 is adopted. Figure 3 are the failure modes of instability of foundation-soil coupling system with wave height H = 1 m and H = 3 m. It is noted that under condition of wave height H = 3 m, the large-diameter monopile overturns shoreward, however under condition of H = 1 m, the foundation overturns seaward, according to investigation of the model tests, Liu and Carter (2000) concluded that under wave loading, the large-diameter cylindrical structure in soft ground may overturns seaward in a certain condition. In previous studies about the ultimate capacity of monopile in soft soil, the foundation overturns shoreward in any case in total stress finite element analyses (Fan, Luan, and Yang, 2006).…”
Section: Finite Element Modelmentioning
confidence: 99%
“…In order to consider the effect of stress path under cyclic loading, a loading surface is assumed in the inner region of the initial yield surface. The model includes the following parameters: M, the slope of critical state line in p-q space; and the slope of the virgin compression line and isotropic recompression line in e-lnp space respectively; v, Poisson's ratio; a model parameter considering OCR degradation of soil under cyclic loading (Carter, Booker, and Wroth, 1980;Liu and Carter, 2000). To minimize the error and improve the convergence, the implicit integration algorithm is adopted in this paper.…”
Section: Integration Algorithm Of Improved Cam-clay Modelmentioning
confidence: 99%
“…This type of approach is clearly expedient and pragmatic, but for engineering application it is generally preferable to the alternative more rigorous approach [2,4,5]. The alternative method, which follows the strict requirements of the theory of elastoplasticity, is too complicated and also often yields less accurate numerical solutions.…”
Section: Soil Deformation Under Repeated Loading With a Large Number mentioning
confidence: 99%